Shanghai Pilot Free Trade Zone and Trade of Steel Products: Influences and Countermeasures - Xu, Runlan; Jiang, Yanqing (Journal of Asian Business Strategy, 2014)
Developed counties are speeding up reconstruction of pattern of international economy and trade in the post-financial crisis era, which brings both great opportunities and challenges to the development of China’s national economy. In order to be geared to TPP and TTIP rules as well as to force domestic reform, the State Council approved the establishment of the China (Shanghai) Pilot Free Trade Zone officially on August 22, 2013. The paper analyzes the influences on China’s steel industry and steel trading industry exerted by China (Shanghai) Pilot Free Trade Zone, and the influential factors mainly contains favorable tax system, financial reform, bulk commodity trading platform and customs supervision mode. Then this paper puts forward four suggestions to China’s steel industry and steel trading industry so that they can seize the current opportunity and utilize the high-quality platform.